RELATIONSHIP BETWEEN HOTELS' DESIGN ADEQUACY AND HOTELIERS' PERCEPTION OF SUSTAINABLE ENERGY MANAGEMENT IN ABUJA, NIGERIA - Shehu, Aisha Isa; Ishiyaku, Bala; Kudan, Hadiza Balarabe; Milala, Sani Inusa (UI Scholars Hub, 2020)
Energy is a sustainability issue receiving primary global concern. Improving energy efficiency and utilizing renewable resources are important in building energy sustainability. An energy-efficient design is a basis for controlling energy efficiency in buildings, and it is highly motivated by the sustainable energy management perception of relevant stakeholders. Hotels have high energy intensities and high working costs. This study investigates the relationship between hotel design adequacy and hoteliers' perception of sustainable energy management in Abuja, Nigeria. The investigation embraces quantitative structure utilizing exploratory and elucidating techniques. The mean ranking and Pearson product-moment correlation results revealed substantial and weak positive correlations (r = 0.601 and r. = 0.257) between design adequacy and hoteliers' perception of importance as well as barriers of sustainable energy management, respectively. However, a negligible negative correlation was found between hotel design adequacy and hoteliers' opinion advantages of sustainable energy management (r. = -0.088). The findings negate the theoretical argument in cognitive dissonance that although hoteliers are conscious of energy issues and the high cost of power generation from back-up generators, they are not interested in investing in sustainable energy management. This study recommends minimizing hotel energy demand through climate-adaptive design and harnessing renewable energy to ensure comfortable and healthy hotel buildings with reduced operating and maintenance costs. Hotel design in the study area reasonably supports energy efficiency. Positive hoteliers' perception of the importance of sustainable energy management is related to improved design adequacy and thus responsible for a positive outcome.